The Effect of Listening to Music on Stress Reduction among Twelfth-Grade Students - Chanmahapon, Kanita; Atsariyasing, Wanlop; Viravan, Natee; Yomaboot, Panida; Hosiri, Tikumporn (Biomedical Sciences and Clinical Medicine, 2022)
Objective: To examine the effects of listening to music on stress reduction among twelfth-grade students. Methods: A quasi-experimental study was conducted. Of 116 twelfth-grade students recruited from a public school in Bangkok, Thailand, 82 completed the study. During a 20-minute period, an intervention group (47 students) listened to music drawing upon nature sounds, whereas a control group (35 students) read about stress reduction techniques. Measurements were made of heart rates and stress levels (using the Thai Stress Test [TST] and a 5-point Likert scale [stress 5-PL]) at baseline and immediately after the activities. A t-test and Chi-squared test for linear-by-linear association were used to compare changes in the stress parameters. Results: Analysis of the baseline and post-intervention data revealed that music listening significantly reduced heart rates and scores for TST and stress 5-PL (p = < 0.001, 0.016, and < 0.001, respectively). However, reading about stress reduction produced no significant lowering of heart rates or scores for TST and stress 5-PL (p = 0.057, 1.000, and 0.070, respectively). In a comparison between the groups, there were no significant differences in the reductions in heart rates or scores for TST and stress 5-PL (p = 0.490, 0.182, and 0.199, respectively). Conclusions: Listening to music for 20 minutes significantly decreased both physical and psychological stress. Nevertheless, the reduction did not differ from that achieved by reading about stress reduction.